Present-Day Challenges in Homeschooling Specialists’ Training in Canada - Tetiana Svyrydova (Educational Challenges)
The article deals with the results of the recent scientific research concerning training of experts for homeschooling in general and its today’s challenges in particular. Canada has been chosen as a target country due to its specific attitude towards homeschooling and its significant experience in specialist and/or teacher training for homeschooling. The urgency of the problem has recently aggravated because of the present-day situation with covid-19 worldwide restrictions in education and subsequent increase in the number of homeschooling families that need expert advice from certified specialists.